PENERAPAN MODEL PEMBELAJARAN EXPERIENTIAL TERHADAP HASIL BELAJAR MATERI CAHAYA DAN SIFAT-SIFATNYA PADA SISWA KELAS V SD 111 PIDOLI DOLOK - Saidah Tunnur Nasution; Parulian Siregar; Resdilla Pratiwi (EDU RESEARCH, 2024)
The aim of this research is to apply and determine the improvement in learning outcomes by using an experiential learning model related to light material and its properties in class V of SD Negeri 111 Pidoli Dolok. The method used is the Classroom Action Research (PTK) method which consists of 2 cycles, namely the first cycle and the second cycle. The population used was 28 class V students. In collecting data, several instruments were used, namely observation sheets and multiple choice tests. Qualitative data analysis was carried out using observation sheets and quantitative data was carried out using validity and reliability tests. The research results show that the application of the experiential learning model is effective and can be improved. The results show that students obtained a classical completeness score of 67.5% in cycle I and a classical completeness score of 72.86% in cycle II.